Effect of using wrestling doll in some snatch movement to judos youth players - Farhan, Ahmed (Journal of Physical Education, 2009)
We use the wrestling doll to learn juniors who to play with compotator at first and to be good in technical movement. Coaches can record notes about wrestler action especially with youngest players to develops action of special wrestler attach it is very important to aloud to him playing with out fear or confuse from compotators reaction. The search aim to advancing level of some snatch movement to judos youth players. We use tow group system (control, experimentalism) with experimental style and choice juniors sample from Al Shoala club (15) years old. The final results are: The units of all programme that use to effecting in experimental grub and technical, repeating movement to judos youth players.